High-speed running density: a new concept - Tierney, P.; Malone, S.; Delahunt, E. (Sport Performance & Science Reports, 2018)
Crrently, there is no described method of distinguishing between HSR volume (distance covered) and HSR intensity (m.min..1) to provide an enhanced degree of specicity for rehabilitation running or conditioning sessions. As such we propose the concept of HSR density. Practical Applications . The addition of HSR density to a GPS report provides greater context as to how the HSR volume of a session has been accumulated. . HSR density may provide a scale of progression in a player's conditioning program upon return from injury. . We suggest that low HSR density performed during RTP sessions will underprepare players for the high density work which characterizes sport-speci c training and match play. . However, we also suggest that low HSR density may be a training mode for enhancing HSR tolerance and improving robustness prior to completing higher density work. Limitations . The data described in this case report may be solely representative of the population reported uppon. . Factors that may in uence the data include, the style of team training and match-play, prescription of rehabilitation running and conditioning, as well as the selected HSR threshold.